Differential effects of the combination of tyrosol with chlorhexidine gluconate on oral biofilms - do Vale, L. R. [UNESP]; Delbem, A. C.B. [UNESP]; Arias, L. S. [UNESP]; Fernandes, R. A. [UNESP]; Vieira, A. P.M. [UNESP]; Barbosa, D. B. [UNESP]; Monteiro, D. R. [UNESP] (Wiley, 2017)
Objective: This study assessed the effect of tyrosol and chlorhexidine gluconate in combination against Candida albicans, Candida glabrata, and Streptococcus mutans in the planktonic state or forming biofilms in vitro. Materials and Methods: Checkerboard assays were performed for determination of minimum inhibitory concentration. Biofilms were cultivated during 24 h on specimens of acrylic resin and hydroxyapatite and treated with the drugs alone or in combination twice a day for 1 min, during 3 days. The antibiofilm effect was determined by quantification of the metabolic activity and cultivable cells. The drug combination was also applied on C. albicans to investigate its action on the number of hyphae. Data were statistically examined by two-way ANOVA and Holm–Sidak test (P < 0.05). Results: The effect of drug combination on planktonic cells was classified as antagonistic for C. albicans and indifferent for the other strains. Also, the drugs were ineffective against the tested biofilms. However, the drug combination showed a synergistic effect in reducing the number of hyphae by C. albicans. Conclusion: The combination of tyrosol with chlorhexidine gluconate was only effective in reducing the number of hyphae by C. albicans, a relevant virulence factor of this species.
Keywords: biofilms; Candida; chlorhexidine gluconate; Streptococcus mutans; Tyrosol